2014
DOI: 10.1530/rep-14-0019
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification alters rabbit foetal placenta at transcriptomic and proteomic level

Abstract: Although numerous studies have demonstrated that cryopreservation alters gene expression, less is known about those embryos that implanted successfully and continued in gestation. To raise the question of the neutrality of this technique, we examine the effects of vitrification through gestation in rabbit before and after the implantation. We monitored the distribution of losses of 569 vitrified morulae, observing that embryos which reach the last pre-implantatory stage are able to implant. However, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 45 publications
6
28
0
1
Order By: Relevance
“…11" " similar to previous ones in our laboratory [27,41]. Our results are lower than those 229" obtained in the pig, which showed about 70% of live embryos in vitro after vitrification 230" [8,22,23].…”
Section: "supporting
confidence: 80%
“…11" " similar to previous ones in our laboratory [27,41]. Our results are lower than those 229" obtained in the pig, which showed about 70% of live embryos in vitro after vitrification 230" [8,22,23].…”
Section: "supporting
confidence: 80%
“…To this end, rabbit embryo banking has allowed the preservation and spread of genetically superior animals over different countries [34] and the possibility of evaluating the genetic gain in maternal lines [4][5][6][7] without cumulative genetic drift variance [35]. Nevertheless, it is known that these techniques induce changes in environ-mental and maternal side effects modifying the embryo gene expression and methylation pattern [19,20,36], the transcriptomic and proteomic placental profile [21], and their viability [29,37], but little is known regarding the long-term effects on the derived progeny. Some authors postulate that these procedures do not induce major anomalies but can lead to morphologic and behavioral features in adult mice derived from frozen embryos [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it must be pointed out that a recent study has reported that embryo cryopreservation and transfer pro-cedures induce changes in the placental function, altering the lipolytic-lipogenic pathway [21], which in fact could affect future organ development, as reported in a series of studies in swine [43,44]. In addition, several authors re-ported modifications in adult organs size due to embryo manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, asynchrony between vitrified embryos and recipient females is applied to obtain higher rates of embryos developed to term [73]. Cryopreservation and transfer procedures affect the RNA expression [74], and consequently the placental transcriptome and proteome [75]. Vitrification also affects foetal survival and growth and modifies the placental development at term [60,76] and growth from birth to adult age [77].…”
Section: Embryo Cryopreservationmentioning
confidence: 99%